Demand-response oriented multi-dimension refined portrait of adjustable resources based on load and survey data fusion - Chen, Shaocong; Gan, Lei; Chen, Canyang; Yu, Kun; Pi, Huimin; Qian, Zi’ang; Dai, Ran (Frontiers in Energy Research, 2022)
Adjustable resources on the demand side of power system plays a vital role to improve operational flexibility of future low-carbon power system integrated with high-penetration renewable generations. While, these demand-side resources may underperform their expected potentials, due to the lack of understanding on consumers’ refined behaviors. Facing the flexibility improvement of future power system, refined portrait structure of single user combining load characteristics and subjective behavior, is constructed with multi-dimension label system from 4 aspects, including energy consumption and load characteristics, adjustable potential, behavioral awareness and user’s nature. Aiming at supplying demand response service, several key indexes are selected and further evaluated here, via data-driven load character analysis and social-survey-driven user’s subjective consciousness mining based on comprehensive evaluation with combination weighting approach. For practical application to demand response decision making, large-scale user adjustable resource is evaluated and classified based on multi-dimension density-based clustering algorithm. Numerical results show the feasibility and rationality of the proposed assessment method.